Implementation of the Small Fishers Empowerment Policy in Tikke Village, Tikke Raya District, Pasangkayu Regency - Rasul, Aras; Rivai, Abdul; Suasa, Suasa (PT. Riset Press International, 2024)
Fishermen still want to live in poverty because of their own desire to experience life itself. Formulation of the problem in the journal How to Implement the Empowerment Policy for Small Fishermen in Tikke Village, Tikke Raya District, research benefits, theoretical benefits and practical benefits. The type of research used in the research is qualitative research. The results of this research are that policy implementation is a crucial stage in the public policy process. . A policy or program must be implemented to have the desired impact or goal. Policy implementation is seen in a broad sense as a public administration tool where actors, organizations, procedures, related parties and resources are organized together to carry out policies to achieve the desired impact or goal. The conclusion of this research is that based on the research results, it can be concluded that the implementation of the Small Fishers Empowerment Policy in Tikke Village, Tikke Raya District, Pasangkayu Regency was found. This did not work well because 4 aspects, namely Communication, Resources, Disposition and Bureaucratic Structure, were used as tools in Edward III's theory. So it can be concluded that the policy has not worked optimally as expected. Therefore, it is necessary to improve fishing equipment such as rumpong.